“The worst thing that has happened to me”: Healthcare and social services professionals confronting death during the COVID-19 crisis - Hernández-Fernández, Carlos; Meneses-Falcón, Carmen (Frontiers in Public Health, 2022)
Objectives This study analyzes the subjective emotional impact COVID-19 deaths have had on healthcare, social services, and funeral services professionals, it explores the different implications, and analyzes the different reactions of health and social care professionals and funeral professionals to the volume of deaths. Methods This work is based on a qualitative, phenomenological, and interpretative approach through in-depth interviews with 42 informants, including 36 social and healthcare professionals, as well as 6 family members of those who died from COVID-19 in Madrid. The interviews were processed through a qualitative, interpretative, categorical analysis. Results Healthcare professionals were overexposed to a significant number of deaths under dramatic circumstances. Many of these professionals had difficulties processing their experiences and expressed the need for psychological help. The fact that certain professionals had previous exposure to high mortality rates was not a protective factor. Some coping differences were seen between healthcare professionals and professionals dedicated to the care of the deceased (undertakers or firemen), particularly in the degree to which they personalized the care they provided. Conclusion The overexposure to death with the circumstances that existed during the state of emergency had a significant emotional impact on the professionals, which can lead to mental health problems in the near term.